2008
DOI: 10.1007/s12010-008-8144-0
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a PHA-Like Chitin-binding Protein from Acacia farnesiana Seeds: A Time-dependent Oligomerization Protein

Abstract: A lectin-like protein from the seeds of Acacia farnesiana was isolated from the albumin fraction, characterized, and sequenced by tandem mass spectrometry. The albumin fraction was extracted with 0.5 M NaCl, and the lectin-like protein of A. farnesiana (AFAL) was purified by ion-exchange chromatography (Mono-Q) followed by chromatofocusing. AFAL agglutinated rabbit erythrocytes and did not agglutinate human ABO erythrocytes either native or treated with proteolytic enzymes. In sodium dodecyl sulfate gel electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Acacia farnesiana lectin-like protein (AFAL) has been purified and classified as PHA-like lectin [1]. Lectins are defined as carbohydrate-binding glyco/proteins that are able to agglutinate cells, without enzymatic activity toward carbohydrate or glycoconjugates [24].…”
Section: Introductionmentioning
confidence: 99%
“…Acacia farnesiana lectin-like protein (AFAL) has been purified and classified as PHA-like lectin [1]. Lectins are defined as carbohydrate-binding glyco/proteins that are able to agglutinate cells, without enzymatic activity toward carbohydrate or glycoconjugates [24].…”
Section: Introductionmentioning
confidence: 99%
“…2; Gallego del Sol, F., Chornet, J. J. C., & Cavada, B. S. PDBcode: 2GDF; to be published) [4,15,[32][33][34][35][36][37][38][39][40][41][42]. A sequence alignment of the sequenced peptides of CRLII against other legume lectin sequence displays a similarity of 53% and 44% with the galactose-specific lectins VML and Rob, respectively (Fig.…”
Section: Protein Sequence and Biochemical Characterizationmentioning
confidence: 97%
“…2 Phylogenetic analysis based on legume lectins sequence alignment. The protein sequence alignment made among partial CRLII sequence with legume seed lectins: CRLI [15], Dgran [35], Dioclea guianensis lectin (Dgui) [37], Dioclea violacea lectin (DVL; Gallego del Sol, F., Chornet, J. J. C., & Cavada, B. S. PDBcode: 2GDF; to be published), Dioclea lehmanii lectin (DLLI) [4], Canavalia gladiata lectin (CGL) [38], ConA [30], ConBr [34], Acacia farnesiana lectin-like protein (AFAL) [39], PHAL [40], PHA [36], Dolichos biflorus lectin (DBL) [41], VML [32], Rob [33], and Dolichos lablab lectin (Dlab) [42]. The alignment and phylogram was generated using CLUSTALW web program Protein Crystallization and X-ray Data Collection…”
Section: Protein Sequence and Biochemical Characterizationmentioning
confidence: 99%
“…Pinus nigra lectin (PNL) was isolated from pine seeds and indirect immunofluorescence assay showed a strong interaction of PNL with hyphal materials of the necrotrophs suggesting their involvement during initial stages of the host-parasite interaction (Nahálkováa et al 2001). A PHA-like chitinbinding lectin was purified from seeds of Acacia farnesiana (Santi-Gadelha et al 2008) with possible role in fungal chitin agglutination. A Castanea crenata agglutinin (CCA) pseudogene was cloned from Japanese chestnut (Nomura et al 2008) and up-regulation of lectins during pest infestation was reported from Picea sitchensis transcriptome (Ralph et al 2006b) and hybrid poplar (Ralph et al 2006a).…”
Section: Lectinsmentioning
confidence: 99%